Anti-Inflammatory Activity of Artocarpus altilis (Parkinson) Fosberg in Wistar Male Rats - Hesti Riasari; Sani Nurlalela; Ginanjar C. Gumilang (Pharmacology and Clinical Pharmacy Research)
Inflammation is a local reaction in vascular tissue characterized by several symptoms, e.g.,  swelling, redness, and pain. Indonesia is one of the countries with high biodiversity, including traditional medicinal plants. Artocarpus altilis is one the plants that is widely used to treat inflammation. There is limited information on biological activity of A. altilis.This study was performed to evaluate anti-inflammatory properties  of A. altilis detached and attached leaves in Wistar male rats. A. altilis was extracted using soxhlet method at 67.4 0C with methanol solvent. Inflammation was induced by the administration of carrageenan to the rats paw. Subsequently, the extract of A. altilis were orally administered. The edema were measured using plethysmometer for 6 hours. We found that there were differences in anti-inflammatory activity between detached and attached leaves. The inhibition of edema in attached leaves were 50% and 53.33% for the concentration of 50 mg and 100 mg, respectively. The greater inhibiton was observed in the detached leaves, with 73.33% and 76.67% inhibition, for the concentration of 50 mg and 100 mg, respectively. Nevertheless, the inhibition percentage was still below diclofenac sodium as a positive control (83.33%).  In conclusion, A. altilis leaves extracts showed good anti-inflammatory properties and has the potential for development of anti-inflammatory drug.  Keywords: Artocarpus altilis, carageenan, inflammation, edema